Analisis Ketepatan Shooting Menggunakan Punggung Kaki Pada Permainan Sepakbola SD Negeri 105 Kendari - Rispan, Basman, Fitriani (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
The aim of this research is to determine the analysis of kick accuracy in football matches at SD Negeri 105 Kendari. This research is quantitative descriptive research with a survey approach. The research sample consisted of 10 people who had undergone withdrawal using total sampling techniques. Data collection tools and techniques are used to test and measure the accuracy of ball kicks in soccer matches. The data analysis technique used is descriptive statistics in the form of percentages using computer tools through the SPSS 20 program. The results of the research show that: the level of shooting accuracy with the feet in soccer matches at SD Negeri 105 Kendari based on test results is in the "very low" category, namely 10% ( 1 soccer player), “less” category. is 10% (1 footballer), the "fairly good" category is 60% (6 footballers), the "good" category is 20% (2 footballers), and the "very good" category is 20% (2 footballers), 0% ( 0 footballers). Based on an average value of 8.4, it can be concluded that the level of shooting accuracy with the feet in football matches at SD Negeri 105 Kendari is in the "sufficient" category.